Management of complete persistent rectal prolapse in children: A comparative study between mesh repair versus suturing rectopexy - Mostafa Gad; Mostafa Nabil Dessouky; Khaled Salah Abdullateef; Osama Abdelazim; Ahmed E Fares; Sherif Nabhan Kaddah; Moutaz Ragab (Wolters Kluwer Medknow Publications, 2024)
Background: Rectal prolapse is a relatively common, usually self-limiting illness in children. Peak incidence is between 1 and 3 years. The primary treatment of rectal prolapse is non-operative. Surgical intervention is needed in long-standing intractable cases of rectal prolapse, rectal pain/bleeding/ulceration and prolapse that needs frequent manual or difficult reduction. The aim of this study was to compare the efficacy and outcome of laparoscopic ventral mesh rectopexy versus laparoscopic suture rectopexy in the management of persistent rectal prolapse in children not responding to conservative management and/or recurrent after sclerotherapy or anal encirclement. Materials and Methods: Twenty-four cases were randomised into two groups at the ratio of 1:1, Group 1 patients were managed by laparoscopic ventral mesh rectopexy, whereas Group 2 cases were managed by laparoscopic suture rectopexy. Patients with primary surgical conditions such as anorectal malformations, Hirschsprung's disease, rectal polyps or masses and Ectopia Vesicae were excluded from the study. Inclusion criteria were complete rectal prolapse cases with failed medical treatment for at least 6 months and/or recurrent after injection sclerotherapy or anal encirclement. Results: In the mesh rectopexy group, one case had recurrence in the form of partial prolapse 3 weeks postoperatively which improved 2 months postoperatively with conservative management, one case had bleeding per rectum 2 months postoperatively, stool analysis was done revealing parasitic infestation which was treated medically. In the suture rectopexy group, one case had one attack of bleeding per rectum on the 2nd day postoperatively which resolved spontaneously and one case was readmitted on the 5th day postoperatively for non-bilious vomiting which improved by medical treatment. No recurrent cases of complete rectal prolapse were reported in both groups. Conclusion: Laparoscopic rectopexy can be an effective modality for the treatment of refractory complete rectal prolapse in children. It is effective, safe and easy. Although the current study has shown that laparoscopic suture rectopexy and mesh rectopexy have nearly the same results, a larger number of patients are needed to compare more deeply between the two groups.